1999
DOI: 10.1034/j.1600-0420.1999.770316.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival after malignant tumors of the orbit and periorbit treated by exenteration

Abstract: ABSTRACT.Purpose: In order to further assess the survival value of orbital exenteration in malignant orbital and periorbital tumors. Methods: The charts of 44 patients exenterated for a neoplasm of the orbit or periorbit were reviewed in a retrospective study. Results:The overall 4-year survival was 45%. 26 patients had free margins on histological examination and 24 patients had developed local recurrence or metastasis. Local recurrence or metastasis were significantly more common in the group with transected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
20
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 24 publications
10
20
3
Order By: Relevance
“…This is lower than other case series, such as Mouriaux et al suggest that tumour-free margins have little effect on survival in patients undergoing exenteration for malignancy, due to the presence of micro-metastases early in disease. 15 Analysis of our data agrees with this view. There was no statistically significant difference in overall survival in patients with clear surgical margins post-exenteration compared to patients without clear margins (p = 0.12).…”
Section: Discussionsupporting
confidence: 93%
“…This is lower than other case series, such as Mouriaux et al suggest that tumour-free margins have little effect on survival in patients undergoing exenteration for malignancy, due to the presence of micro-metastases early in disease. 15 Analysis of our data agrees with this view. There was no statistically significant difference in overall survival in patients with clear surgical margins post-exenteration compared to patients without clear margins (p = 0.12).…”
Section: Discussionsupporting
confidence: 93%
“…This finding confirms those of Rahman et al 4 and Mouriaux et al 7. One explanation for this finding is that despite having prevented local recurrence, micro-metastasis may have occurred prior to surgery.…”
Section: Discussionsupporting
confidence: 91%
“…This is lower than the rates of positive permanent margins between 28 and 47% reported in other series. 6,17,19 One possible explanation for this is that the multidisciplinary approach to tumor resection typically used at this tertiary referral cancer center enabled additional surgical procedures to be performed at the same time as the exenteration in order to optimize tumor control. In our series, multivariate analysis showed that the presence of a positive final surgical margin was the only potential factor that was associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, positive final surgical margins have not been associated with a worse prognosis in other series. 6,17 It may be hard to compare numbers between different retrospective series because of the heterogeneity of inclusion criteria. This is possibly due to lower overall rates of positive margins in this series as mentioned above, as well as higher rate of micrometastasis of other tumor types such as melanoma, malignant sarcomas, adenoid cystic carcinoma, sinonasal tumors, primary orbital tumors, and lacrimal tumors, which were not included in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation